IMPROVING CLASSROOM MATERIALS DESIGN FOR VOCATIONAL ENGLISH TEACHERS AT SAMPANG VOCATIONAL HIGH SCHOOLS - Nurir Rohmah (INOVISH JOURNAL, 2019)
Improving the content and classroom materials design for English Classrooms at any vocational high school level is a tough job. English teachers at SMK levels found it challenging to integrate their classrooms materials to fulfill the vocational needs of their students. No denying to the fact that Vocational English has set a different framework compare to general English classes at the similar level of education. This study aims as a joint research partnership and as well as a platform to improve and create variety of English Vocational Materials for SMK classes in Sampang area. Around 7 public vocational high schools were involved in this study, providing a thorough information of its studentsâ€™ needs for ESP purposes. The materials included knowledge about syllabus writing and the creation of independent teaching materials in the classroom as well as the implementation of reading, writing, and listening and speaking which are targeted to two different goals, UNBK and ESP improvements. The activity of developing English teaching materials is also expected to improve the final results of UNBK Students in English subjects. The study has resulted in the findings of challenges of teaching and developing materials for ESP classes, learning and teaching weaknesses triumph with the models, and the possible future solutions for ESP teaching at SMK level. The study also resulted in the initiative project collaboration with MKKS SMK in Sampang area to pioneer Sampang Vocational Camp 2020. Â